问题
解答题
|
答案
(1)
+[(1 12
+1 6
)+1 12
],1 3
=
+[(1 12
+2 12
)+1 12
],1 3
=
+[(1 12
+2 12
)+1 12
],4 12
=
+1 12
,7 12
=
;2 3
(2)28×
,26 27
=(27+1)×
,26 27
=27×
+26 27
,26 27
=26+
,26 27
=26
;26 27
(3)
-(9 14
+2 7
),3 14
=
-9 14
-2 7
,3 14
=
-9 14
-4 14
,3 14
=
;1 7
(4)85×
,3 86
=(86-1)×
,3 86
=86×
-3 86
,3 86
=3-
,3 86
=2
;83 86
(5)236÷
+236÷5 9
,5 41
=236×
+236×9 5
,41 5
=236×(
+9 5
),41 5
=236×10,
=2360;
(6)
×5 9
÷8 15
,4 9
=
×5 9
×8 15
,9 4
=
;2 3
(7)45÷(1-
)÷(1-2 5
),3 8
=45÷
÷3 5
,5 8
=45×
×5 3
,8 5
=120.